Effect of Training on Creatine Kinase enzyme level of Syrian Purebred Arabian Horses (Damascus University Journal of agriculture sciences, 2021)
The Experiment Was carried out in Damascus Horse race track- Al Demas- Damascus Countryside. The study included (29) Purebred Arabian horses at the ages of 2-9 years which were divided into three groups according to their training backgrounds.The horses underwent a six-month training program and Creatine kinase values were taken over four periods (before, after, 30min and 60 min of exercise) with a 15-day interval between exercises to determine alterations of CK levels during training.Results showed that there was a significant effect (P
Keywords: Arabian horse; Creatine kinase; Training